Hubungan Internet Addiction Dengan Motivasi Belajar Siswa SMA Negeri 1 Negara - Gede Rizky Wismaya Pradipha; Luh Gde Evayanti; Rima Kusuma Ningrum (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2025)
In the digital era, individuals find it easier to access information. The convenience provided by the internet often leads people to become complacent, resulting in excessive usage and potential addiction. Internet usage is common among students and significantly impacts their learning motivation. Learning motivation refers to the drive or enthusiasm that students exhibit in their educational pursuits, shaped by personal expectations, goals, and needs. When students possess positive motivation, they tend to demonstrate greater eagerness and enthusiasm for learning and are more actively engaged in class activities. This study aims to explore the relationship between internet addiction and the learning motivation of students at SMA Negeri 1 Negara. The sample consists of students who met the study's inclusion and exclusion criteria, selected through purposive sampling, totaling 178 respondents. This research adopts an observational analytic design with a cross-sectional approach. The results of the study show that the majority of students at SMA Negeri 1 Negara experienced a moderate level of internet addiction, accounting for 77.5%, followed by a severe level at 16.9%, and a mild level at 5.6%. Meanwhile, in terms of learning motivation, most students fell into the moderate category at 81.5%, followed by the high category at 16.9%, and the low category at 1.7%. The Spearman correlation test indicated a weak but significant negative relationship between the level of internet addiction and students' learning motivation, with a p-value of < 0.003 and a correlation coefficient of -0.222. This suggests that the higher the level of internet addiction experienced by students, the lower their learning motivation tends to be. These findings highlight that uncontrolled internet use can negatively impact students' enthusiasm and engagement in the learning process. Nevertheless, most students still demonstrated a moderate level of learning motivation, indicating an awareness and ability to self-regulate against the adverse effects of excessive internet use.